Morphology of the antennal sensilla of Rhus gall aphids (Hemiptera: Aphidoidea: Pemphiginae): A comparative analysis of five genera - Yang, Zi-Xiang; Chen, Xiao-Ming; Feng, Ying; Chen, Hang (Zootaxa, 2009)
Rhus gall aphids induce sealed galls which are rich in tannic acid and have been widely used for chemical and medicinal purposes. Identification of these aphids at the genus and species levels can be a challenge due to their morphological similarity and unusually complex life cycles. The external morphology of the antennae of 11 taxa was examined by both light and scanning electron microscopy, each antenna comprising a basal scape, a pedicel, and an elongate flagellum of three or four segments covered with secondary sensilla of five morphologically distinct types. Aphids with Rhus chinensis as primary host have five antennal segments; those with R. potaninii and R. punjabensis var. sinica as hosts have six segments. In Schlechtendalia species, each flagellar segment is covered with a large placoid sensillum that is separated by sunken grooves and appears as irregular plates with numerous microtrichia. In Nurudea species, the secondary sensilla look like annular rings, with the surface almost fully covered with microtrichia. Floraphis meitanensis has annular sensilla with smooth surfaces, and each ring is surrounded by longer microtrichia. Meitanaphis and Kaburagia species have a large sheet secondary sensillum occupying half to three-fourths of the area of each flagellar segment. The secondary sensilla of two species of Meitanaphis showed great differences indicating the need for revision of the genus.